Nephroprotective Effect of Placental Cryoextract When Simulating Acute Renal Failure in Rats - Vaskovych, Artem M.; Repin, Mykola V.; Marchenko, Larysa M.; Govorukha, Tetiana P.; Pasieshvili, Nana M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 183.